Предмет: Алгебра,
автор: Ладушки123
1.
2.
3.
Ответы
Автор ответа:
0
1. tg (a + b) = (tg a + tg b) / (1 - tg a tg b)
tg (a - b) = (tg a - tg b) / (1 + tg a tg b)
(tg x + tg y)/tg(x + y) + (tg x - tg y) / (tg(x-y) = (tg x + tg y) / (tg x + tg y) * (1 - tg x tg y) + +(tg x - tg y) / (tg x - tg y) * (1 + tg x tg y) = 1 - tg x tg y + 1 + tg x tg y = 2
2. sin (π - 2a) + 2 cos(3/2π + a)sin(3/2π-a) = sin 2a + 2 sin a (-cos a) = 2 sin a * cos a - 2 sin a cos a = 0
3. cos^4 a/2 - sin^4 a/2 = (cos ² a - sin ²a)(cos² a + sin² a) = cos²a - sin²a = cos 2a
tg (a - b) = (tg a - tg b) / (1 + tg a tg b)
(tg x + tg y)/tg(x + y) + (tg x - tg y) / (tg(x-y) = (tg x + tg y) / (tg x + tg y) * (1 - tg x tg y) + +(tg x - tg y) / (tg x - tg y) * (1 + tg x tg y) = 1 - tg x tg y + 1 + tg x tg y = 2
2. sin (π - 2a) + 2 cos(3/2π + a)sin(3/2π-a) = sin 2a + 2 sin a (-cos a) = 2 sin a * cos a - 2 sin a cos a = 0
3. cos^4 a/2 - sin^4 a/2 = (cos ² a - sin ²a)(cos² a + sin² a) = cos²a - sin²a = cos 2a
Автор ответа:
0
1
(tgx+tgy((1-tgxtgy)/(tgx+tgy)+(tgx-tgy)(1+tgxtgy)/(tgx-tgy)=1-tgxtgy+1+tgxtgy=2
2
sin2a-2sinacosa=sin2a-sin2a=0
3
(cos²a/2-sin²a/2)(cos²a/2+sin²a/2=cosa*1=cosa
(tgx+tgy((1-tgxtgy)/(tgx+tgy)+(tgx-tgy)(1+tgxtgy)/(tgx-tgy)=1-tgxtgy+1+tgxtgy=2
2
sin2a-2sinacosa=sin2a-sin2a=0
3
(cos²a/2-sin²a/2)(cos²a/2+sin²a/2=cosa*1=cosa
Похожие вопросы
Предмет: Математика,
автор: scelovek
Предмет: Обществознание,
автор: Muhofiz
Предмет: Химия,
автор: charxappy1
Предмет: Биология,
автор: МИЛЕНА5262
Предмет: Математика,
автор: Аноним